Immunohistochemical characterization of polyclonal antibodies against Enteromyxum leei and Enteromyxum scophthalmi (Myxozoa: Myxosporea), intestinal parasites of fish - Estensoro, Itziar; Redondo, Mª José; Álvarez-Pellitero, Mª del Pilar; Sitjà-Bobadilla, Ariadna (Journal of Fish Diseases, 2014)
The enteric myxozoan parasites Enteromyxum leei (Diamant, Lom et Dyková) and Enteromyxum scophthalmi Palenzuela, Redondo et Alvarez-Pellitero are responsible for high weight loss in infected fish, which leads to subchronic disease and low mortality rates in gilthead sea bream (GSB), Sparus aurata L., and to high mortality rates in turbot, Psetta maxima (L.). The detection of initial parasite stages in histological sections is particularly difficult, but can be simplified by means of specific antibodies. Rabbit polyclonal antibodies (pAbs) were raised agains tE. scophthalmi and E. leei, and direct enzyme linkedimmunosorbent assay (ELISA) and immunohistochemistry were used to characterize their sensitivity and specificity. Both pAbs were adsorbed (apAb) with non-infected intestines to avoid nonspecific labelling of fish tissues and to improve their specificity. The highest titre obtained in ELISA was 1: 32 000 for apAb-Eleei and 1:16 000 for apAb-Escoph. Working dilutions in immunohistochemistry were 1:1000 for apAb-Eleei and 1:8000 for apAb-Escoph. Both apAbs labelled proliferative and sporogonic stages with high specificity. apAb-Escoph was very specific, whereas apAb-Eleei cross-reacted with Sphaerospora dicentrarchi Sitjà-Bobadilla et Alvarez-Pellitero and Sphaerospora testicularis SitjàBobadilla et Alvarez-Pellitero, suggesting the presence of shared antigens. These pAbs stand as new tools for antigenic characterization and the diagnosis of both Enteromyxum species. This work was funded by the Spanish Ministry of Science and Innovation (MICINN) through the project AGL2009-13282-C02-01. Additional funding was obtained from the ‘Generalitat Valenciana’ (research grants PROMETEO 2010/006 and ISIC 2012/003). I. E. received a Spanish PhD fellowship (FPI) from MICINN. Peer Reviewed